Peningkatan Partisipasi Mahasiswa melalui Implementasi Desain Didaktis Materi Integral Lipat Tiga Berbantuan GeoGebra dan Nearpod - Rahma Nasir; Pathuddin Pathuddin; Welli Meinarni; Alfisyahra Alfisyahra; Desrin Lebagi (Universitas Tadulako, 2022)
The absence of digital visualisation in mathematical concepts leads on students' difficulty in learning and affect on lack of students' participation. The study aims to increase students' participation through the implementation of triple integral didactical design assisted by using GeoGebra and Nearpod. GeoGebra is a tool used to help students in finding mathematical concepts as well as demonstration and visualization. In addition, in this didactical design, there are several problem practices and quizzes that were provided by using recorded video from lecturers and processed into digital quizzes on Nearpod. The subjects were 65 students in the third semester of Mathematics Education Study Program who have never taken triple integral course. The research method used was Didactical Design Research. The data were collected by triangulation of observation, interview, and documentation. Based on the results of the study, it can be concluded that the percentage of students' participation increases through the implementation of triple integral didactical design assisted by using GeoGebra and Nearpod.